EHypertension: A prospective longitudinal multi‐omics essential hypertension cohort. Issue 2 (18th April 2022) - Sun, Wei; Wang, Yifeng; Zhang, Haifeng; Sheng, Yanhui; Fan, Jingyi; Gu, Mingxia; Tian, Yunfan; Zhang, Yuqing; Ma, Hongxia; Yin, Xiaorong; Sun, Kangyun; Ding, Zheng; et al.
Abstract : eHypertension is an essential hypertension cohort with multiple layers of omics data collected and will be followed up longitudinally. Randomized antihypertensive intervention has been set up in eHypertension. eHypertension is a unique cohort for studying the etiology and clinical outcome of hypertension. Interventions in eHypertension may contribute to the development of prediction models for personalized antihypertensive treatment.